Radiosensitization by Histone H3 Demethylase Inhibition in Diffuse Intrinsic Pontine Glioma - Katagi, Hiroaki (Clin Cancer Res, 2019)
PURPOSE: Radiation therapy (RT) has long been and remains the only treatment option for diffuse intrinsic pontine glioma (DIPG). However, all patients show evidence of disease progression within months of completing radiation therapy. No further clinical benefit has been achieved using alternative radiation strategies. Here we tested the hypothesis that histone demethylase inhibition by GSK-J4 enhances radiation-induced DNA damage, making it a potential radiosensitizer in the treatment of DIPG. EXPERIMENTAL DESIGN: We evaluated the effects of GSK-J4 on genes associated with DNA double-strand break (DSB) repair in DIPG cells by RNA sequence, ATAC sequence, and quantitative real-time PCR. Radiation-induced DNA DSB repair was analyzed by immunocytochemistry of DSB markers γH2AX and 53BP1, DNA repair assay, and cell cycle distribution. Clonogenic survival assay was used to determine the effect of GSK-J4 on radiation response of DIPG cells. In vivo response to radiation monotherapy and combination therapy of RT and GSK-J4 were evaluated in patient-derived DIPG xenografts. RESULTS: GSK-J4 significantly reduced the expression of DNA DSB repair genes and DNA accessibility in DIPG cells. GSK-J4 sustained high levels of γH2AX and 53BP1 in irradiated DIPG cells, thereby inhibiting DNA DSB repair through homologous recombination pathway. GSK-J4 reduced clonogenic survival and enhanced radiation effect in DIPG cells. In vivo studies revealed increased survival of animals treated with combination therapy of RT and GSK-J4 in compared to either monotherapy. CONCLUSIONS: Together, these results highlight GSK-J4 as a potential radiosensitizer and provide a rationale for developing combination therapy with radiation in the treatment of DIPG.